Pendidikan Kritis Menurut Mansour Fakih Dan Relevansinya Terhadap Pendidikan Islam - partahian partahian; Koiy Sahbudi Harahap; Elisah Pahutar; Ahmad Muda Harahap; Nurkhoiriyah Dalimunthe (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
The increasingly advanced world requires critical, broad, and in-depth thinking. To achieve this, education is needed that not only develops skills but also critical thinking. One of those who formulated critical education is Mansour Fakih, an Indonesian educational figure and social movement concerned with the world of Indonesian education. Some of his ideas have inspired Indonesian government policies, especially in the field of education, namely the birth of the concept of independent learning as a reference for the Indonesian education curriculum. This study aims to explore his thoughts on the concept of critical education. This study uses a literature study sourced from all works written by Mansour Fakih. Works written by Mansour Fakih served as primary data sources. Meanwhile, all documents in the form of books, journals, and research results concerning Mansour Fakih served as secondary data sources. The findings of this study show that critical education, according to Mansour Fakih, is an education for critical liberation. Education does not shackle students from developing their creativity. Critical education, according to Mansour Fakih, must be experiential learning, not patronizing, and dialogical. 2). This kind of education is very relevant to Islamic education which emphasizes free education without shackles because the nature of humans is free.